PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Survei pada Nasabah PT Bank Tabungan Negara (Persero) Tbk Cabang Solo) - Kunthi Daruwati, Sunarso & Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Bank Tabungan Negara (Persero) Tbk Branch Solo as banking institutions arealways working to improve customer satisfaction by providing optimum service andincrease customer confidence. The purpose of this study was to analyze the significanceof the impact of service quality on customer confidence in PT Bank Tabungan Negara(Persero) Tbk Branch Solo, analyze the significance of the impact of service quality andcustomer confidence in the customer satisfaction in PT Bank Tabungan Negara(Persero) Tbk Branch Solo, analyzing the mediating effect of customer confidence in theimpact of service quality on customer satisfaction in PT Bank Tabungan Negara(Persero) Tbk Branch Solo. This study uses survey method, the type of data usedquantitative and qualitative data, the data source used primary data and secondary data.The population in this study were all customer PT Bank Tabungan Negara (Persero) TbkBranch Solo in January 2017. The number of samples in this study as many as 100customers, accidental sampling technique using random sampling. Data collectionmethods are used: questionnaires and documentation. Data analysis technique used totest the validity, reliability test, classic assumption test, and path analysis. In conclusion:1) There is significant influence service quality to customer confidence. 2) There was asignificant effect of service quality on customer satisfaction. 3) There is significantinfluence on customer satisfaction customer confidence. 4) The client's trust mediates theimpact of service quality on customer satisfaction.Keywords: service quality, trust, customer satisfaction